Segregação socioespacial: os condomínios horizontais na cidade de São Carlos/SP - Nardin, Juliana de (2011)
This dissertation focuses the closed horizontal condominiums and subdivisions in the city of São Carlos that appeared in the 1970s consolidating itself as the form of housing of highincome classes that seek parts far from the center to live within the walls. In 1976 in São Carlos, it was deployed Parque Sabará the first enterprise of this tipe since then, the condominiums expanded and hold large areas of the city. They are located as in portions more remote as in the consolidated urban area. This dynamic is increasing in many Brazilian cities, as evidenced by the growing production of work aimed at this issue. This way, there are discussions and questions the social perspective, as an ingredient of socio-spatial segregation, or in relation to the legality of the establishment of these enterprises, that do not have specific legislation that regulates us. Therefore, the dissertation refers to the study and analysis of closed residential subdivisions and condominiums in São Carlos, and the transformations inserted in the context of the deployment of these enterprises. The research is based in literature search, documentary, photographic and visits to investigate the production of urban space from the closed condominiums and subdivisions set in a dynamic real estate production. This study was guided by the discussion of socio-spatial segregation and the capitalist production of space that impose occupation patterns that spread and are responsible for maintaining the capital.